The first documented case of fulminant liver failure from herpes simplex virus in an immunocompromised patient taking to facitinib. Issue 5 (23rd July 2020) - Beck, Jared; Haggard, Heath; Membreno, Fernando
Abstract: Herpes simplex virus induced fulminant liver failure is a rare aetiology. With the advent of new immunomodulator medications like tofacitinib, there is much to be learned about the risk of herpes simplex reactivation, screening and treatment strategies for patients who present in fulminant liver failure. We present a case of a 33‐year‐old female recently started on tofacitinib for rheumatoid arthritis who presented to the hospital with fulminant liver failure. She was proactively started on intravenous acyclovir on admission. Herpes simplex virus‐II polymerase chain reaction came back positive. Liver biopsy was grossly positive for acute necrotising herpes simplex virus hepatitis. Patient subsequently underwent successful orthoptic liver transplant. Conservative immunosuppression regimen was pursued in the setting of active viraemia. Mild acute T‐cell mediated rejection ensued, but mycophenolate therapy was deferred in the setting of active herpes simplex viraemia. Patient was re‐dosed with intermittent boluses of methylprednisolone and carefully monitored tacrolimus levels with complete resolution of mild rejection. Herpes simplex virus polymerase chain reaction became undetectable on hospital day 51 with transition to oral acyclovir indefinitely. To our knowledge, this is the first documented case of a patient on tofacitinib, presenting with fulminant liver failure secondary to herpes simplex reactivation. Management of post‐transplant immunosuppression was challenging due to the presence of active herpes simplex viraemia. A modified, low‐intensity immunosuppression protocol was used based on low‐dose tacrolimus, standard methylprednisolone taper with transition to prednisone, without mycophenolate or induction with basiliximab. We believe this low‐intensity regimen allowed for definitive treatment of herpes simplex viraemia. In the setting of fulminant liver failure secondary to herpes simplex hepatitis, early suspicion, initiation of empiric acyclovir and consideration of early transfer to a liver transplant centre had a direct impact on our patient's survival. Future studies should investigate the significance and frequency of latent viral reactivation on tofacitinib and if formal screening recommendations for latent viral infections, particularly herpes simplex virus, are warranted.